Effect of Glomus microcarpum in Relation to the Biomass Production of Wheat Plants - Dhungana, Nirmala; Raut, Prakash; Singh, Anjana (Nepal Journal of Science and Technology, 2010)
Many studies have shown that mycorrhizal inoculations enhance the growth and nutrient uptake by plants. However, in Nepal, the focus of study is being given to the leguminous plants. To study the effect of vesicular-arbuscular mycorrhiza (VAM) in the biomass production of wheat, common VAM fungus Glomus microcarpum was inoculated in four varieties of wheat (Triticum aestivum) (i.e. WK 810, WK 1320, WK 1357 and WK 2089); the VAM spores being isolated by wet sieving and decanting process. Recording effects were started after one week of seed sowing, then weekly for growth parameters and on 15 days interval for edaphic parameters. In all cultivars, increased root and shoot biomass were recorded in inoculated ones compared to their non-inoculated counterparts. The reaction to the G. microcarpum inoculants was not different significantly for all cultivars when comparison was made on them on 89th day after inoculation, where the biomass values were recorded maximum. Also, phosphorus and organic matter contents of soil related inversely to the VAM fungal spore number in the soil and the root infection. This study demonstrates the potential use of G. microcarpum as biofertilizer in nutrient poor soils. Key words: vesicular-arbuscular mycorrhizae; Glomus microcarpum; Triticum aestivum DOI: 10.3126/njst.v9i0.3169 Nepal Journal of Science and Technology 9 (2008) 79-83